Effects of Auditory Cueing on Cadence and Gait Pattern. (December 2020) - Carballo, Andrei; Chang, Matthew; Hirmiz, Brian; Lambright, Nicolette; Lee, Vivian; Lewis, Marla; Nguyen, Martin; Gothong, Matthew; Soangra, Rahul
A large portion of the population participate in gait rehabilitation, especially those with conditions such as increased fall risk such as stroke, or Parkinson's Disease. Some studies have shown that auditory cues help improve gait and reduce fall risk, but relationship with gait patterns is missing. In this study, eight participants walked at their preferred cadence and at increased and reduced cadence by 20%. We found that step length and step width were not significantly different in all walking conditions. Decreased cadence resulted in an increase of swing time, stance time, stride time, and stance to swing ratio, and a decrease in stride length. Increased cadence resulted in a decrease in stance time, stride time, swing time, and stance to swing ratio, and an increase in stride length. The results suggest there is a strong correlation between auditory cues and gait patterns that can improve rehabilitative processes in the future.